TRPM4-mediated control of FcεRI-evoked Ca 2+ elevation comprises enhanced plasmalemmal trafficking of TRPM4 channels in connective tissue type mast cells - Rixecker, Torben M.; Mathar, Ilka; Medert, Rebekka; Mannebach, Stefanie; Pfeifer, Alexander; Lipp, Peter; Tsvilovskyy, Volodymyr; Freichel, Marc (Scientific reports, 2016)
TRPM4 proteins form Ca2+-activated non selective cation (CAN) channels that affect transmembrane Ca2+-influx by determining the membrane potential. Tight control of the intracellular Ca2+ concentration is essential for mast cell responses. In this study, we analyzed the expression of TRPM4 in peritoneal mast cells (PCMC) as a model for connective tissue type mast cells with respect to FcεRI-evoked calcium changes and the subcellular localization of fluorescently labeled TRPM4 using two viral transduction systems before and following antigen stimulation. Our results show that TRPM4 is expressed in PCMCs, is an essential constituent of the endogenous CAN channels in PCMCs and regulates antigen-evoked increases in intracellular calcium that are significantly enhanced in TRPM4-deficient PCMCs. Compared to PCMCs analyzed before antigen stimulation, the cells depict a substantially increased localization of TRPM4 proteins towards the plasma membrane after FcεRI stimulation. Thus, TRPM4 functions as a limiting factor for antigen evoked calcium rise in connective tissue type mast cells and concurrent translocation of TRPM4 into the plasma membrane is part of this mechanism.